THE RELATIONSHIP OF KNOWLEDGE, SUPERVISION, AND SOCIALIZATION WITH OCCUPATIONAL ACCIDENTS AT PT. TATAMULIA NUSANTARA INDAH - Arum Budiarti; Cahya Arbitera; Dwi Mutia Wenny (Universitas Darussalam Gontor, 2019)
In Indonesia there is an increasing trend in the number of occupational accidents, BPJS Ketenagakerjaan noted, in 2014 as many as 106,383 cases of work accidents occurred in Indonesia, in 2015 there were 110,285 cases, in 2016 amounted to 101,367 cases, in 2017 the reported number of accidents reached 123,041 the case, while throughout 2018 the number of occupational accidents rose to 173,105 cases with claims of Work Accident Insurance (JKK) of Rp 1.2 trillion. The purpose of this research was to determine the relationship between knowledge, supervision, and socialization of OHS programs to work accidents in construction workers at PT. Tatamulia Nusantara Indah Southgate Apartment Tanjung Barat Project. The research method used is quantitative research with a cross sectional approach with a sample of 85 workers. The results of univariate data analysis showed that work accident rates (54.1%) and knowledge levels were high (61.2%), supervision (55.3%) and socialization of OHS (52.9%) were good. Bivariate data analysis using Chi Square test showed that there was a significant relationship between knowledge (p-value 0.012 and OR = 3.636), supervision (p-value 0.002 and OR = 4.511), and socialization of OHS (p-value 0.011 and OR = 3.500) with work accidents. Keywords: Accident, Knowledge, OHS, Socialization, Supervision